Transcriptomic Characterization of the Effects of Selenium on Maize Seedling Growth - Dou, Lingling; Tian, Zailong; Zhao, Qin; Xu, Mengting; Zhu, Yiran; Luo, Xiaoyue; Qiao, Xinxing; Ren, Rui; Zhang, Xianliang; Li, Huaizhu (Frontiers in Plant Science, 2021)
Abstract: Selenium (Se) is a trace mineral element in soils that can be beneficial to plants in small amounts. Although maize is among the most economically important crops, there are few reports on the effects of Se on maize seedling growth at the molecular level. In this study, the growth of maize seedlings treated with different concentrations of Na2SeO3 was investigated and physiological characteristics were measured. Compared with the control, a low Se concentration promoted seedling growth, whereas a high Se concentration inhibited it. To illustrate the transcriptional effects of Se on maize seedling growth, samples from control plants and those treated with low or high concentrations of Se were subjected to RNA sequencing. Differently expressed genes (DEGs) analysis revealed that 239 up-regulated and 106 down-regulated genes in the low Se treatment groups, while there were 845 up-regulated and 1686 down-regulated DEGs in the high Se treatment groups. GO and KEGG annotation analysis showed that a low concentration of Se-stimulated expression of ‘DNA replication’ and ‘glutathione (GSH) metabolism’ related genes. A high concentration of Se repressed expression of auxin signal transduction and lignin biosynthesis related genes. qRT-PCR results showed that in the low Se treatment, ‘auxin signal transduction’, ‘DNA replication’, and lignin biosynthesis related genes were up-regulated 1.4-57.68 fold compared to the control, while the high Se concentration treatment down-regulated lignin biosynthesis and auxin signal transduction regulated genes 1.6-16.23 fold compared to the control. Based on these transcriptional differences and qRT-PCR validation, it was found that a low dosage of Se may promote maize seedling growth but becomes inhibitory to growth at higher concentrations. This work lays a foundation for the mechanisms underlying the effects of Se on maize seedling growth.